2020
DOI: 10.15244/pjoes/120155
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Rapid Anaerobic Fermentation on Animal Slurry for Biogas Production and Storage of Biogas Slurry

Abstract: A study was designed aiming at the degradation of organic matter in liquid phase of pig manure, the inactivation of pathogenic microorganisms and biogas production at different storage temperatures. A low cost rapid anaerobic fermentation, and biogas sewage storage system was constructed. After the four-day anaerobic fermentation, three treatments were set up: the average temperature of spring and autumn (16.1ºC), summer (25ºC), and winter (0.6ºC) in Yantai City was used as storage temperature for 90 days, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The average concentration of N, P, K and Mg in the residue are 0.847 %, 0.28 %, 2.09 %, and 0.4767 mg/kg respectively (Table 4). Liang et al (2021) recorded 0.059 %, 0.05% and 0.052% for N, P and K respectively for animal wastes fermentation residue. Marchioro et al (2018), reported higher value of N, P, and K with solid state anaerobic digestion of poultry litters.…”
Section: Tablementioning
confidence: 92%
“…The average concentration of N, P, K and Mg in the residue are 0.847 %, 0.28 %, 2.09 %, and 0.4767 mg/kg respectively (Table 4). Liang et al (2021) recorded 0.059 %, 0.05% and 0.052% for N, P and K respectively for animal wastes fermentation residue. Marchioro et al (2018), reported higher value of N, P, and K with solid state anaerobic digestion of poultry litters.…”
Section: Tablementioning
confidence: 92%